2018
DOI: 10.1016/j.yfrne.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone involvement in feeding regulation, overeating and obesity

Abstract: Obesity is strongly associated with ill health, primarily caused by consumption of excessive calories, and promoted (inter alia) by gamma-amino-butyric-acid (GABA) stimulating food intake by activating GABA receptors (primarily with α3 and α2 subunits) in the hypothalamic arcuate nucleus and paraventricular nucleus. Allopregnanolone is a potent positive GABA receptor modulating steroid (GAMS). As reviewed here, elevated allopregnanolone levels are associated with increases in food intake, preferences for energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 133 publications
1
16
0
Order By: Relevance
“…Levels of allopregnanolone have been associated with changes in food intake and eating disorders in humans 82 96 . In rats, administration of allopregnanolone increased the feeding latency, as well as the meal duration and the preference for fat 97 98 . Although the specific mechanisms underlying the changes in feeding behavior have not been elucidated, neurosteroid’s best characterized molecular function is the modulation of GABA signaling at GABA A receptors 99 .…”
Section: Hypothalamic Astrocytes Sexual Dimorphismmentioning
confidence: 97%
“…Levels of allopregnanolone have been associated with changes in food intake and eating disorders in humans 82 96 . In rats, administration of allopregnanolone increased the feeding latency, as well as the meal duration and the preference for fat 97 98 . Although the specific mechanisms underlying the changes in feeding behavior have not been elucidated, neurosteroid’s best characterized molecular function is the modulation of GABA signaling at GABA A receptors 99 .…”
Section: Hypothalamic Astrocytes Sexual Dimorphismmentioning
confidence: 97%
“…To further explore the role of the GABA(A)R in T cell activation leading to proliferation we studied the effects of the neurosteroid allopregnanolone on human and murine T cells. Neurosteroids are implicated in various processes in the CNS [28][29][30]. It has been shown that allopregnanolone potentiates the actions of αβ-containing GABA(A)Rs at nanomolar concentrations and ρ-containing receptors at micromolar concentrations [31,32].…”
Section: Allopregnanolone Inhibits Human and Mouse T Cell Proliferationmentioning
confidence: 99%
“…Because of their ability to modulate multiple signaling pathways, 3α-hydroxy, 5α-reduced neurosteroids have been shown to play important roles in physiological and pathophysiological regulation of stress, mood and feeding behavior (reviewed in Gunn et al, 2011 ; Mody and Maguire, 2012 ; Bäckström et al, 2014 ; Holmberg et al, 2018 ). In addition, and of particular interest for the focus of this review, 3α-hydroxy, 5α-reduced neurosteroids have been shown to have therapeutic potential for use in treatment of neurodegenerative and neurological diseases.…”
Section: α-Hydroxy 5α-reduced Neurosteroids As Regulators Of Gaba mentioning
confidence: 99%